Tom Henderson Wells research notes - Wells, Tom Henderson, 1917-1971.
Carbon copies of research notes for Wells's book, Commodore Moore and the Texas Navy (1960); together with an index to the notes.
Naval officer and author.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Moore, Edwin Ward, -- 1811-1865.; Texas. -- Navy; Authors; Naval officers